Flood Risk Analysis in Şanlıurfa City Centre (Architecture Image Studies, 2026)
In recent years, Turkey has become a place where loss of life and property due to natural disasters has increased. The rise in losses, particularly from floods, stems from construction in riverbeds and poor planning decisions. One of the most recent examples is the flood that occurred in the city center of Şanlıurfa, one of Turkey's major cities, on March 15, 2023, which resulted in the loss of 17 lives and material losses. The study gained importance because land use decisions in the city center of Şanlıurfa, which was selected as the study area, were made without considering flood risk, increasing the potential for sudden rainfall to turn into floods. To this end, the urban development of Şanlıurfa was examined in terms of flood risk, and the Süleymaniye and Göl neighborhoods, which have the highest potential for impact, were examined in detail. The flood risk analysis map, created using Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) methods, shows that risk increases in areas close to rivers, with high rainfall, and dense construction. According to the risk analysis map, approximately 32% of the study area consists of low-risk areas, 62% of medium-risk areas, and 6% of high-risk areas. In areas where flood risk cannot be prevented, it is recommended that existing structures be evacuated or demolished based on their risk status, and that settlement in safer areas identified in place of risky structures be encouraged.